2012
DOI: 10.1007/s11606-012-2209-z
|View full text |Cite
|
Sign up to set email alerts
|

Lichen Sclerosus in a Breast Cancer Survivor on an Aromatase Inhibitor: A Case Report

Abstract: Lichen sclerosus is a commonly misdiagnosed disease that is characterized by thinned, hypopigmented, crinkled skin that often forms a figure-eight shape around the vaginal and anal openings. We present a case of advanced lichen sclerosus in a 53-year-old female patient prescribed a nonsteroidal aromatase inhibitor after the excision of a breast cancer tumor. We present a diagnostic approach to lichen sclerosus by recognizing its common figure-eight pattern, and we review the known causes and treatment of liche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
4
0
1
Order By: Relevance
“…15 Indeed, LS has been identified to occur with greater frequency in menopause and other lowestrogen states, such as in patients on aromatase inhibitors for cancer treatment. 16,17 Interestingly, high-estrogen states have been associated with protection against T-cell-mediated autoimmune conditions. 18 PNinf has previously been identified in 2 studies and proposed as a potentially novel histologic feature of lichen sclerosus.…”
Section: Discussionmentioning
confidence: 99%
“…15 Indeed, LS has been identified to occur with greater frequency in menopause and other lowestrogen states, such as in patients on aromatase inhibitors for cancer treatment. 16,17 Interestingly, high-estrogen states have been associated with protection against T-cell-mediated autoimmune conditions. 18 PNinf has previously been identified in 2 studies and proposed as a potentially novel histologic feature of lichen sclerosus.…”
Section: Discussionmentioning
confidence: 99%
“…Complaints related to the skin such as rash, pruritus, dry skin, and acne appear less frequently [2]. However, rare cutaneous adverse events such as cutaneous vasculitis [1, 3, 4, 5], erythema nodosum [6], subacute cutaneous lupus erythematosus [7], lichen sclerosus vulvae [8], erythema multiforme [9], and erythema multiforme-like eruption [10] have been reported. A previous report suggested that inhibition of the estrogen effect, which prevents the pathogenesis of vasculitis, may paradoxically induce vasculitis [4].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Onset of dermatology-related adverse events ranged from 2 days to 9 months. Commonly reported side effects included unspecified rash, pruritus, various immune-mediated reactions, vulvovaginal atrophy, and alopecia ( Balagula et al, 2011 ; Budel et al, 1986 ; Crockett and Burkemper, 2011 ; De Placido et al, 2018 ; Jhaveri et al, 2007 ; Moscetti et al, 2015 ; Ooi and Jaffar, 2019 ; Paridaens et al, 2003 ; Pellegrini et al, 2009 ; Pokhai et al, 2014 ; Potter and Moore, 2013 ; Rossi et al, 2013 ; Schadler et al, 2018 ; Sestak et al, 2014 ; Shoda et al, 2005 ; Sonke et al, 2018 ; Stein et al, 1990 ; Stratakis and Chrousos, 1994 ; Tominaga et al, 2003 ; Trancart et al, 2008 ; Tryfonidis et al, 2016 ; Williams and Leslie, 1987 ; Wong et al, 2008 ; Yang et al, 2020 ; Zarkavelis et al, 2016 ).…”
Section: Dermatologic Adverse Eventsmentioning
confidence: 99%
“…Treatment includes improving vaginal elasticity and lubrication. In women for whom estrogen therapy is contraindicated, therapeutic options include vaginal dilators, pelvic floor physical therapy, moisturizers, lubricants, thermoablative fractional CO2 laser, U.S. Food and Drug Administration–approved intravaginal dehydroepiandrosterone, and the novel selective estrogen receptor modulator ospemifene ( Biglia et al, 2015 ; 2017 ; Cook et al, 2017 ; Ferreira et al, 2019 ; Moegele et al, 2012 ; Witherby et al, 2011 ) Lichen sclerosus is another vulvovaginal dAE that may present similarly to GSM and has been described in association with AI use in a case report ( Potter and Moore, 2013 ). Treatment options include potent topical corticosteroids and topical immunomodulators, such as calcineurin inhibitors ( Potter and Moore, 2013 ).…”
Section: Dermatologic Adverse Eventsmentioning
confidence: 99%